Unreasonable: Black Lives, Police Power, and the Fourth Amendment - Carbado, Devon W. (The New Press, 2022)
Intro -- Prologue -- Introduction -- Chapter One -- Chapter Two -- Chapter Three -- Chapter Four -- Chapter Five -- Chapter Six -- Chapter Seven -- Acknowledgments -- Notes -- Index.